2008
DOI: 10.1097/mpg.0b013e31817fcb56
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Adolescents With Treated Coeliac Disease: Influence of Compliance and Age at Diagnosis

Abstract: Compliance with GFD is an essential factor to obtain optimal QOL. Psychosocial and educational support should be provided for patients having difficulties strictly adhering to GFD. Early CD onset and diagnosis is associated with better physical health, lower CD-associated burden and fewer social problems, indicating the importance of the earliest CD diagnosis possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 23 publications
13
111
2
1
Order By: Relevance
“…Our results suggest that the HRQL found in the general population of adult celiac subjects may be lower than that observed in patients recruited in a hospital setting, giving rise to the hypothesis that periodic medical check-ups improve the quality in life for these patients by encouraging a stricter compliance with a gluten-free diet. In fact, the correct maintenance of a gluten-free diet has repeatedly been shown to be an independent factor associated with a better quality of life among celiac patients, both in children (31) and adults (19,20,22,32,33). Our study did …”
Section: Discussionsupporting
confidence: 45%
“…Our results suggest that the HRQL found in the general population of adult celiac subjects may be lower than that observed in patients recruited in a hospital setting, giving rise to the hypothesis that periodic medical check-ups improve the quality in life for these patients by encouraging a stricter compliance with a gluten-free diet. In fact, the correct maintenance of a gluten-free diet has repeatedly been shown to be an independent factor associated with a better quality of life among celiac patients, both in children (31) and adults (19,20,22,32,33). Our study did …”
Section: Discussionsupporting
confidence: 45%
“…30 In addition, numerous studies in pediatric and adult celiac patients have repeatedly shown that a gluten-free diet achieves not only symptom relief, but also improvements in HRQoL. [30][31][32][33] We did not evaluate the efficacy of dietary intervention in every patient who participated in our survey, and studies evaluating this issue are currently lacking. It is tempting to speculate whether identification and long-term exclusion of individual food triggers could also lead to improvements in HRQoL, as suggested in a recent study that assessed EoE with a nonspecific instrument.…”
Section: Discussionmentioning
confidence: 99%
“…However, bec ause of the c ontinuing mucosal abnormalities, they remain at risk of developing the c omplic ations of CD. Indeed, adolesc ents who do not adhere to a GFD have a lower quality of life [120] . Immunohistochemical labeling has helped to define an abnormal prognostic profile of intra-epithelial lymphoc ytes in the small bowel muc osa, so-c alled "refrac tory c eliac disease, type 2 (RCD 2)" c harac terized by an aberrant c lonal IEL population with loss of IEL antigens.…”
Section: Refractory Diseasementioning
confidence: 99%